PENGARUH DANA PIHAK KETIGA, PENYALURAN KREDIT DAN TINGKAT SUKU BUNGA KREDIT TERHADAP PROFITABILITAS PADA LEMBAGA PERKREDITAN DESA (LPD) SE-KECAMATAN ABIANSEMAL TAHUN 2017-2019 - Putu Nadia Citra Pradnyasari; Ni Ketut Muliati (UNHI Press, 2021)
Profitability is the ability of a company to generate profits from its capital. This study aims to examine how the effect of third party funds, credit distribution, and credit interest rates on profitability. The sample in this study was 33 LPDs with three years of research observation. The sampling method used is purposive sampling method. The data analysis technique used in this research is descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, F test, and t test. Based on the results of the simultaneous analysis test, third party funds, lending, and credit interest rates have a significant effect on profitability and partially third party funds and lending have no effect on profitability, while credit interest rates have a positive and significant effect on profitability.